The Experiments with Natural Compounds in Secondary School Chemistry Education – Opinions of Secondary School Teachers - Opatová, Michala; Hybelbauerová, Simona (Scientia in educatione, 2020)
The paper focuses on the opinions of secondary school chemistry teachers of ‘Experiments with natural compounds in chemistry education’. The teachers answered the questions on the theoretical and experimental teaching of this topic in an interactive questionnaire. The main objective of our research was to investigate which experiments with natural compounds the teachers use in their classes, if teachers extend this topic to areas other than given in the curriculum document, the Framework Education Programme, and where teachers find the inspirations for their experiments. The results will be used, among others, to make a compilation of innovated or not well known experiments with natural compounds and instructions for these experiments.